Inclusive social development : the next generation of policies for overcoming poverty and reducing inequality in Latin America and the Caribbean (UN ECLAC SantiagoCL, 2015)
Aims to evaluate the region's progress towards overcoming poverty and inequality, identifying contributing factors, limitations and outstanding issues, in order to support national efforts in these areas.
Keywords: SOCIAL DEVELOPMENT